20.4k views
1 vote
11) The solution to 3(x - 8) + 4x = 8x + 4 is

a) 12 b) 28 c) -12 d) -28

11) The solution to 3(x - 8) + 4x = 8x + 4 is a) 12 b) 28 c) -12 d) -28-example-1
User Kartic
by
5.4k points

2 Answers

5 votes
3(x-8) +4x = 8x+4
3x- 24 + 4x -8x =4
-x =4 +24
x = - 28
So the answer is (d).
User Jjmirks
by
5.4k points
6 votes

Answer:

d) -28

Explanation:

Distribute the "3" on the left side of the equation, then isolate the variable on one side:

3(x - 8) + 4x = 8x + 4

3x - 24 + 4x = 8x + 4

7x - 8x = 4 + 24

-x = 28

x = -28

User Rupok
by
4.6k points